PELAKU BULLYING DAN NILAI KARAKTER SISWA SMP NEGERI 13 PEKANBARU - Witra Lusiana; Zulfan Saam; Raja Arlizon (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: One of the most common forms of violence in schools is bullying. Bullying is a deliberate act of harming others and there is an element of satisfaction for the bullies. The lack of character education in schools causes many students to engage in bullying that can harm the bullies and his own victims. Applying the value of the character to the student is something that should be done in the world of education. Because of the many problems that occur with the character of students at school, encouraging writers to do research about it. The purpose of this research is to know the description of bullies behavior in view of physical bullying, verbal, and mental as well as to know the description of bullies student characters at SMPN 13 Pekanbaru. The subject in this study amounted to thirty students. This research uses descriptive method with quantitative approach. Data collection techniques in the form of questionnaires. To analyze data using the percentage formula. The results showed that the behavior of bullies are in the medium category and the character value of bullies are in the high category. The conclusions of this study are a higher aspect of verbal bullying, then physical, and mental. For the character value of bullying students, the six aspects are in the high category of tolerance, friendly/communicative, caring, honest, social and responsibility. Discipline aspect is in the medium category. It is advisable for school to better monitor students development so that bullying behavior does not happen again.Key Word: Bullies, Character Value